Protocols for Dual Tracer PET/SPECT Preclinical Imaging - Blower, Julia E.; Bordoloi, Jayanta K.; Rigby, Alex; Farleigh, Matthew; Kim, Jana; O'Brien, Hugh; Jackson, Jonathan; Poyiatzis, Constantinos; Bezer, James; Sunassee, Kavitha; Blower, Philip J.; Livieratos, Lefteris (Frontiers in Physics, 2020)
Background: Multi-tracer PET/SPECT imaging enables different modality tracers to be present simultaneously, allowing multiple physiological processes to be imaged in the same subject, within a short time-frame. Fluorine-18 and technetium-99m, two commonly used PET and SPECT radionuclides respectively, possess different emission profiles, offering the potential for imaging one in the presence of the other. However, the impact of the presence of each radionuclide on scanning the other could be significant and lead to confounding results. Here we use combinations of 18F and 99mTc to explore the challenges posed by dual tracer PET/SPECT imaging, and investigate potential practical ways to overcome them. Methods: Mixed-radionuclide 18F/99mTc phantom PET and SPECT imaging experiments were carried out to determine the crossover effects of each radionuclide on the scans using Mediso nanoScan PET/CT and SPECT/CT small animal scanners. Results: PET scan image quality and quantification were adversely affected by 99mTc activities higher than 100 MBq due to a high singles rate increasing dead-time of the detectors. Below 100 MBq 99mTc, PET scanner quantification accuracy was preserved. SPECT scan image quality and quantification were adversely affected by the presence of 18F due to Compton scattering of 511 keV photons leading to over-estimation of 99mTc activity and increased noise. However, 99mTc:18F activity ratios of > 70:1 were found to mitigate this effect completely on the SPECT. A method for correcting for Compton scatter was also explored. Conclusion: Suitable combinations of injection sequence and imaging sequence can be devised to meet specific experimental multi-tracer imaging needs, with only minor or insignificant effects of each radionuclide on the scan of the other.